Monitoring of Volatile Organic Compounds at Gyeongju: A Historical and Tourist Place in South Korea - Kyo Seo, Young; Narayana Suvarapu, Lakshmi; Ok Baek, Sung (Asian Journal of Chemistry, 2014)
Volatile organic compounds monitoring in ambient air is an important task to the environmental researchers throughout the world due to their toxic effects to the human beings. Our literature survey revealed that not much attention has paid in the monitoring of volatile organic compounds at tourist and/or historical places in the world. The present study predicts the air quality in terms of the ambient concentrations volatile organic compounds at Gyeongju, a historical/tourist city in South Korea and recognized as world heritage site by the UNESCO. The extensive sampling and analysis of volatile organic compounds at this city reveals that only 34 volatile organic compounds are found at beyond the method detection limit among the 68 measured volatile organic compounds and only 8 volatile organic compounds including benzene, toluene, ethylbenzene and m-, p-xylenes (BTEX) are found in over 90 % detection frequency. We also compared the concentrations of BTEX obtained in present study with other tourist, historical and the UNESCO world heritage sites in the world. The concentrations of BTEX found in Gyeongju are much lower than the other cities in the world with which are compared. The questionnaire with the tourists regarding air quality at Gyeongju also tells us that over 97 % of the surveyed tourists are happy with the quality of air at sampling sites. It is suggested that the usage of electric car/bus for the public transport to further reduction in the concentration of volatile organic compounds in ambient air of Gyeongju. The major advantage of this study is it predicts the accurate exposure of volatile organic compounds by the tourists, because the sampling of volatile organic compounds is carried out with personal exposure samplers by moving around the tourist spots which is not fixed at a single spot.